Prediction of residual stresses and distortions induced by nitriding of complex 3D industrial parts. Issue 1 (2015) - Depouhon, P.; Sprauel, J.M.; Mermoz, E.
Abstract: A multi-scale and multi-physical model, based on finite element methods, is developed to predict the residual stresses and distortions induced by the nitriding of industrial parts. It describes the diffusion of nitrogen and carbon, the precipitation of nitrides and carbides and the dissolution of previously formed precipitates. The residual stresses and distortions are then derived from the calculated volumetric and thermal eigenstrains accompanying the precipitations. This requires accounting for the creep existing in the treatment. The model is applied to the nitriding of complex helicopter gear box components. The realized measurements are in very good agreement with the theoretical predictions.